Análise econômica e experiência comparativa entre agricultura de precisão e tradicional - Werner, Valmir (2007)
The study was developed in the farm Anna, located in the municipal district of Não-me-Toque RS, in the period included among the crops of 2002/03 and 2005/06. In the precision farming worked areas were generated yield maps of the culture, with information collected through sensors that equip the harvester, maps of soil fertility, with are based in geo-referenced soil samplings of soils, and maps of fertilizers application in variable rates, according to the prescriptions of the soil samplings in the precision agriculture system. In the present case study whether it compared the economically results of the soy crop in the two areas, handled in precision agriculture, with the results of the other areas of the farm, managed by the traditional farming (averages). The main results of the study demonstrate that in the precision farming the medium cost, of the soy production, was 0,3% smaller in relation to the handling in traditional farming. The liquid margin was higher in that in R$ 81,18 ha-1, representing a difference of 18,4%. The medium of the soy culture was more lucrative in 36,0% in AP and 32,2% in AT. The medium profitability rose from 3,3% in the traditional management to 3,9%, when adopting the AP. This resulted in a investment return of 2,9 soy crops in the 256 hectare handling, in this system.